FISH FAUNA OF GUNUNG HALIMUN NATIONAL PARK REGION: ADDITIONAL INFORMATION ON THE UTILIZATION*[Fauna Ikan Taman Nasional Gunung Halimun: Informasi Tambahan Tentang Pemanfaatannya] - Ike Rachmatika; Djadja S Sjafei; W Nurcahyadi (BERITA BIOLOGI, 2002)
Gunung Halimun National Park is known to be the area of headwaters of a number of rivers/streams originate. However,there is no information about the fishes living in these rivers systems. In this regard, a series of ichthyofauna study was conducted from 1996 to 2002 in Cikaniki, Cimaja/Cisarua, Cisukawayana, Ciberang, Cidurian and Cibareno that covered 94 sampling stations. Method that was used was Catch Per Unit of effort (CPU) where electric fishing gear (and) cast net, trap were used.Forty fish species belonging to 16 families and 26 genera have been found. Gobiidae, the diadromous fishes, was dominant, comprising 14 species or 35 %, followed by Cyprinidae comprising 5 species or 12.5 %.These Gobioid fishes were derived from Cisukawayana, Cimaja, and Cibareno River, where these rivers flow south to the Indian Ocean. It was found that Paray, Rasbora aprotaenia; Beunteur, Puntius binotatus; Bogo, Channa gachua; Lele, Clarias batrachus; Kehkel, Glyptothorax platypogon; Soro, Tor tambra; Bungkreng/ Ikan Seribu Poecilia reticulata and Paris, Xiphoporus helleri were found in common in rivers flowing north and south, and Lentipes as well as Schismatogobius marmoratus extend their range to Java (new record for Java). The utilization of fishes for food by local people is presented including Gobioid fishes, which are at the juvenile stage (called as impun) are utilized as a part of their food source.